ANTESEDEN DAN KONSEKUENSI DARI RAPPORT - Freddy Irawan; Ovy Noviati Nuraini Magetsari (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2018)
As a main factor in rapport and satisfaction, commitment has been given much attention. The primary data was gathered by online questionnaires and collected from 204 respondents who are being customers of Bank BNI in Jakarta. This research used hypothesis testing as a research design. The cross-sectional data and purposive sampling are used as the sampling method. Data were analyzed by using Structural Equation Method (SEM). Finding and contribution in this research showed that all of commitment have positive effects towards rapport and satisfaction. Rapport has positive and significant effect to satisfaction. Implications and suggestions for future research are discussed.